Identification of exonic regions in dna sequences an approach using cross-correlation and noise suppression by discrete cosine transform (Research, Society and Development, 2020)
To identify the exonic regions in the DNA sequence of Chromosome 23, filtering techniques are used. DCT is a technique with the ability to remove noise from signals as shown in [Saraiva et al., 2018], in addition, noise suppression with DCT is not enough in itself, so in this work a new method of identifying exonic regions using cross correlation with DCT together with an FFT-based bandpass filter to decrease signal noise and find exonic regions.